The effect of financial institution development on economic growth: Evidence from MENA region - Hanoun, Raed; Taher, Hanadi (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of financial institutional development on economic growth in 12 Middle East and North Africa (MENA) countries—Lebanon, Saudi Arabia, Turkey, the United Arab Emirates, Bahrain, Morocco, Jordan, Kuwait, Oman, Qatar, Tunisia, and Egypt—over the period from 1990 to 2023. Using panel data techniques, the analysis begins with pooled ordinary least squares, fixed effects models, and Driscoll–Kraay robust fixed effects models. Given the presence of heteroskedasticity and serial correlation in the pooled ordinary least squares model, robust estimates are obtained through the Driscoll–Kraay method. The results reveal a significant positive relationship between financial institutional development and economic growth, with a one-unit improvement in financial institutions associated with a 2.381-unit increase in economic growth. These findings underscore the importance of strengthening financial institutions as a driver of economic performance in the MENA region. The study contributes to the literature by offering updated empirical evidence over a long time span and highlighting the role of macroeconomic factors in shaping growth outcomes.